Construction of Performance Tester for Fuel Injector of Laboratory Diesel Engine - ตะพาบน้ำ กรยุทธ; สิทธิพงศ์ สายชล (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The construction of a diesel injector tester for use with the objectives of 1) creating a diesel injector tester that can spray fuel into mist and can be used to check the working conditions of various diesel engine fuel injectors. In this research, the injector pressure value was tested according to the standard performance value of the injector pressure in the data. [3] The fuel injectors used in the test were Nissan SD22 nozzle injectors and Isuzu 4JA1 hole injector injectors, which have a standard value of 120 bar. 2) studying the satisfaction of users of the diesel fuel injector performance tester. The population and sample were expert technicians and establishments, a total of 10 people, by purposive selection. The research instruments were data recording and questionnaires. The statistics used in the research were mean, standard deviation, and percentage. The experimental results found that when testing the diesel injector tester of the fuel injector of Nissan car model SD22 pin type and the fuel injector of Isuzu car model 4JA1 hole type using the VE pump to test the standard pressure value of the fuel injector of Nissan car model SD22 and the injector used in the experiment was a pin type injector with the highest difference in injector pressure not exceeding 5 bar and the fuel injector of Isuzu car model 4JA1 was a hole type injector with the highest difference in injector pressure not exceeding 4 bar. The pressure value of both types of injectors is within the standard value that can be used when compared to the standard value specified from the car data. For the quality of the diesel fuel injector performance tester, the overall average value is at a high level (3.86) and the evaluation of the satisfaction of the users with the tester found that they were satisfied with the overall level at the highest level (4.54).